Epigallocatechin-3-Gallate Inhibits Matrix Metalloproteinase-9 and Monocyte Chemotactic Protein-1 Expression Through the 67-κDa Laminin Receptor and the TLR4/MAPK/NF-κB Signalling Pathway in Lipopolysaccharide-Induced Macrophages - Li, Ya-Fei; Wang, Hao; Fan, Yi; Shi, Hao-jie; Wang, Qi-Ming; Chen, Bing-rui; Khurwolah, Mohammad Reeaze; Long, Qing-qing; Wang, Si-Bo; Wang, Ze-Mu; Wang, Lian-Sheng (Cellular physiology and biochemistry, 2017)
Background/Aims: Epigallocatechin-3-gallate (EGCG), a major catechin found in green tea, has been shown to prevent cardiovascular diseases. Previously, Matrix metalloproteinase-9 (MMP-9), monocyte chemotactic protein-1 (MCP-1) and toll-like receptor 4 (TLR4) were confirmed to play an important role in atherosclerosis and plaque instability. Both TLR4 and its negative regulator, Toll-interacting protein (Tollip), could be mediated by EGCG. The present study aimed to examine the effect of physiological concentration of EGCG (1 µM) on the expression of MMP-9 and MCP-1 in lipopolysaccharide (LPS)-induced macrophages and the potential mechanisms underlying its actions. Methods: The RAW264.7 cell line was used. Western blot was used to determine MCP-1, TLR4, Tollip, Mitogen-activated protein kinase (MAPK) and Nuclear factor-κB (NF-κB) protein expression. MMP-9 activity was assayed by gelatine zymography. The mRNA expression of MMP-9 and MCP-1 was measured by realtime polymerase chain reaction (RT-PCR). Results: EGCG (1 µM) significantly suppressed the expression of MMP-9 and MCP-1 and inhibited MAPK and NF-κB in LPS-induced macrophages but was blocked by Tollip silencing. The expression of LPS-induced MMP-9 and MCP-1 and the phosphorylation of the ERK1/2, P38 and NF-κB pathway proteins decreased after TLR4 siRNA treatment. Furthermore, EGCG mediated TLR4 and Tollip expression through binding to 67-kDa laminin receptor (67LR). Conclusion: The results of our study suggested that EGCG (1 µM) suppresses the TLR4/MAPK/NF-κB signalling pathway, decreases the expression of the plaque instability-mediating cytokines MMP-9 and MCP-1, and might prove to be effective in stabilizing atherosclerotic plaque.